The lion in the shadows : E.J. Brickell of Illinoistown, Truckee and Spokane Falls - Brickell, James E. (Gray Dog Press, 2018)
"A throng of people stood near the entrance of the Spokane Methodist Episcopal Tabernacle on Sunday, September 27, 1891. Inside the church was packed, with standing room only, but it was not for the usual Sunday service. It was the largest funeral that Spokane had ever seen at that point in the city's history; the funeral of its first millionaire, and wealthist citizen. He whose body lay in the coffin had been: President of the Traders National Bank; President of the Truckee Lumber Co.; President of the Donner Lumber and Boom Co.; President of the Verdi Flume Company; President of Spokane Cracker Co.; President of Spokane Bottling Co.; President of Spokane Falls Water Power Co.; President of Spokane Falls Lumber & Manufacturing Co.; President of the Spokane Mill Co.; President of Holley, Mason, Marks & Co.; President of Baum & Co.; President of the Old Dominion Mining Co.; President of the Columbia Mining Co.; President of the Security Loan and Trust Co. It has been said that his investments and entrepreneurship came at a critical time when the first investors of Spokane Falls had exhausted their capital and almost lost their faith in the city. His was a material contribution to the maintenance of Spokane's growth in the decade of the 1880s."